Improving Students’ Mathematical Reasoning Ability and Self-Regulated Learning through Geogebra-Assisted Problem-Based Learning Model on Junior High School - Cahyani, Yayah Dwi; Sabandar, Jozua; Yuliani, Anik (IKIP Siliwangi, 2026)
Reasoning is a skill that students must possess to improve their ability in solving mathematics problems related to everyday life. Meanwhile, self regulated learning skills is aims to increase their sense of responsibility for their own learning. This research aims to improve both of these abilities through the geogebra assisted the problem-based learning, so the students can be better understand about concepts that taught by the teacher, take responsibility, and build their self regulated learning. The researcher used a quasi-experimental design with a pretest-posttest approach involving both experiment and control groups, that each consisting of 25 student in eighth-grade from SMP EL Fitra Bandung. The first step that reseacher take is given a pretest to both of class, after that continue to give experiment class with geogebra assisted the problem based learning method and control class with a conventional method. The research instruments used were a mathematical reasoning essay test about system linear equation in two variabels (SPLDV) and a self regulated scale. The integration of geogebra software is in line with current technological advancements and make the student more interesting when learning many subject at school specially in mathematic program. The results showed that students who received geogebra assisted problem-based learning method performed better in reasoning ability compared to those who received conventional method. However, there was no significant difference in self regulated learning between the two groups, indicating that both the experimental and control groups experienced an increase in self regulated learning.